Solid Acids from Persulphated and Perchlorated Physical Mixtures of Zirconium and Titanium Hydroxides - Gamal M.S. El Shafei; Christine A. Philip (Adsorption Science & Technology)
Calcination at 650°C of a physical mixture of zirconium and titanium hydroxides led to the formation of the corresponding oxides, monoclinic zirconia and anatase. The adsorption of perchlorate or persulphate anions (as 0.05, 0.1, 0.2 or 0.4 M aqueous solutions) before calcination did not inhibit crystallization; however, perchlorate anions activated the formation of rutile in addition to the predominant anatase phase. Indeed, the adsorption of perchlorated anions prior to calcination allowed the thermodynamically less stable tetragonal phase of zirconia to be detected in addition to monoclinic zirconia at ambient temperature. In contrast, the adsorption of persulphate anions before calcination stabilized the tetragonal phase with no rutile phase being detected in this case. Infrared spectroscopy showed that adsorbed S 2 O 8 2– anions were held more strongly by the solid than ClO 4 − anions which tended to decompose when the solid was calcined. The acidities of the solid acids produced because of S 2 O 8 2– or ClO 4 − anion adsorption were studied via the adsorption of pyridine (pK a = 5.3) from cyclohexane solution. The amounts and strengths of the acid sites formed during persulphate treatment were higher than those resulting from perchlorate adsorption. The strength of the acid sites formed on samples calcined before loading with S 2 O 8 2– or ClO 4 − anions showed no significant differences. Variations detected in the structural aspects arising from S 2 O 8 2– or ClO 4 − anion adsorption were reflected in the texture as assessed by nitrogen adsorption at −196°C.